Status of Taiwan and the Evolution of Taiwanese Identity - A. S. Kaimova; I. E. Denisov (Сравнительная политика)
The Taiwan issue, which originated from China’s civil war, not only defines the complex relationship between Beijing and Taipei but also has significant implications for security and stability in the Asia-Pacific region. The article examines the evolution of Taiwan’s status and the formation of Taiwanese identity within the context of the escalating geopolitical confrontation between China and the United States. The study focuses on historical, political, and cultural factors that have shaped Taiwanese identity, offering a fresh perspective that goes beyond previous binary ideological assessments. The authors highlight the influential role of historical heritage, including Chinese cultural influence, Polynesian culture, the Japanese colonial period, and Taiwan’s interaction with the United States, in shaping a unique hybrid Taiwanese identity. The analysis presented in the paper makes it evident that the Taiwan issue is not only intensified by the increasing US support for «separatist forces» on the island but also by the inherent dynamics of great-power competition. Taiwan aims to leverage global uncertainty to strengthen its international standing and assert its own agency. The findings of this study demonstrate that amid the intense US-Chinese competition, the expression of Taiwanese identity becomes magnified, thereby further complicating the pursuit of a peaceful resolution to the Taiwan issue in the long run. The conclusion derived from this research is relevant for understanding and forecasting the future dynamics of the situation in the Taiwan Strait.